1995
DOI: 10.1007/bf00299174
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of microscopically nonradical, subtotal pancreaticoduodenectomy (Whipple's resection) for treatment of pancreatic head tumors

Abstract: From 1983 to 1992 a total of 240 patients with a pancreatic head tumor underwent laparotomy to assess the resectability of the tumor. In 44 patients the tumor was not resected because of distant metastases (n = 20) or major vascular involvement or local tumor infiltration (n = 24) not detected during the preoperative workup. A palliative biliary and gastric bypass was performed in these patients. All other patients underwent a subtotal (Whipple's resection, n = 164) or total (n = 32) pancreaticoduo-denectomy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
5

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 13 publications
0
28
0
5
Order By: Relevance
“…In two recent studies, one from The Johns Hopkins Hospital, Baltimore (USA) and the other from our institution (Academic Medical Center, Amsterdam, The Netherlands), surgical bypass and palliative resection were compared [16,17]. Both studies are retrospective and therefore suffer from methodologic flaws.…”
Section: Postoperative Complications and Mortality After Palliative Smentioning
confidence: 99%
See 1 more Smart Citation
“…In two recent studies, one from The Johns Hopkins Hospital, Baltimore (USA) and the other from our institution (Academic Medical Center, Amsterdam, The Netherlands), surgical bypass and palliative resection were compared [16,17]. Both studies are retrospective and therefore suffer from methodologic flaws.…”
Section: Postoperative Complications and Mortality After Palliative Smentioning
confidence: 99%
“…This is another important factor that could influence survival. From these two studies it was concluded that the perioperative morbidity and mortality after palliative resection were acceptable, and therefore a more aggressive approach should be offered to patients with pancreatic cancer [16,17].…”
Section: Postoperative Complications and Mortality After Palliative Smentioning
confidence: 99%
“…Abscesses may contribute to septicaemia, which is found in 1–4% of patients [39, 44]. Abscesses commonly arise from anastomotic leak at the pancreatoduodenostomy, the hepaticojejunostomy, the duodenojejunostomy, the gastrojejunostomy or the jejunojejunostomy and often herald as right subhepatic or left subdiaphragmatic collections [51, 52].…”
Section: Intra-abdominal Abscessmentioning
confidence: 99%
“…The relatively high incidence of post-operative complications refers to the complexity of surgery with multiple anastomoses of different types and the rather poor nutritional status and high background co-morbidity of the patient group [10, 32, 39, 41, 42]. Medical complications evoked as a consequence of surgery include cardiac problems (angina, infarction and arrhythmias), cardiovascular accidents (strokes), cardiorespiratory distress, renal dysfunction, pneumonia, thrombosis, pulmonary embolism, psychological disturbances and hepatic and metabolic dysfunction.…”
Section: General Complications Following Pancreatic Resectionmentioning
confidence: 99%
See 1 more Smart Citation